BMM1312 Computer Programming - Fatimah, Dzaharudin; Ummu Kulthum, Jamaludin (Penerbit UMP, 2017)

(untitled)
This module was developed from lab notes for a semester course at Universiti Malaysia Pahang—BMM1312 Computer Programming that serves two goals. The first goal is to introduce programming to Mechanical Engineering students. The second goal is to expose students to the conceptual tools in programming. These skills and exposure are important since programming and computing are becoming increasingly in demand in all scientific and engineering disciplines. In this course, students will learn how to develop computer programs with ANSI C using a software called ‘Chide’